A US hospital budget impact analysis of a skin closure system compared with standard of care in hip and knee arthroplasty - Sadik K; Flener J; Gargiulo J; Post Z; Wurzelbacher S; Hogan A; Hollmann S; Ferko N (Dove Medical Press, 2018)
Kay Sadik,1 Jana Flener,2 Jeanine Gargiulo,3 Zachary Post,4 Steven Wurzelbacher,5 Andrew Hogan,6 Sarah Hollmann,6 Nicole Ferko6 1Ethicon Inc., Health Economics Market Access, Somerville, NJ, USA; 2Proliance Orthopedic Associates, Renton, WA, USA; 3Anderson Orthopaedic Clinic, Arlington, VA, USA; 4Department of Orthopedic Surgery, Sidney Kimmel Medical College at Thomas Jefferson University, Philadelphia, PA, USA; 5Trihealth Orthopaedic and Sports Institute, Cincinnati, OH, USA; 6Cornerstone Research Group Inc., Burlington, ON, Canada Background: Medicare’s mandatory bundle for hip and knee arthroplasty necessitates provider accountability for quality and cost of care to 90 days, and wound closure may be a key area of consideration. The DERMABOND® PRINEO® Skin Closure System (22 cm) combines a topical skin adhesive with a self-adhering mesh without the need for dressing changes or suture or staple removal. This study estimated the budget impact of the Skin Closure System compared to other wound closure methods for hip and knee arthroplasty. Methods: A 90-day economic model was developed assuming 500 annual hip/knee arthroplasties for a typical US hospital setting. In current practice, wound closure methods for the final skin layer were set to 50% sutures and 50% staples. In future practice, this distribution shifted to 20% sutures, 20% staples, and 60% Skin Closure System. Health care resources included materials (eg, staplers, steri-strips, and traditional/barbed sutures), standard or premium dressings, outpatient visits, and home care visits. An Expert Panel, comprised of three orthopedic physician assistants, two orthopedic surgeons, and a home health representative, was used to inform several model parameters. Other inputs were informed by national data or literature. Unit costs were based on list prices in 2016 US dollars. Uncertainty in the model was explored through one-way sensitivity and alternative scenario analyses. Results: The analysis predicted that use of Skin Closure System in the future practice could achieve cost savings of $56.70 to $79.62 per patient, when standard or premium wound dressings are used, respectively. This translated to an annual hospital budgetary savings ranging from $28,349 to $39,809 when assuming 500 arthroplasties. Dressing materials and postoperative health care visits were key model drivers. Conclusions: Use of the Skin Closure System may provide cost savings within hip and knee arthroplasties due to decreases in resource utilization in the postacute care setting. Keywords: budget impact analysis, wound closure, knee arthroplasty, hip arthroplasty, hospital, economic, wound dressings, costs, postacute care